2018
DOI: 10.1186/s13020-018-0205-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and anti-tumor activity of a polysaccharide isolated from Dendrobium officinale grown in the Huoshan County

Abstract: BackgroundPolysaccharides are carbohydrate chains composed of linked monosaccharide units. Accumulating studies report that polysaccharides isolated from Dendrobium officinale have a variety of functions. However, the composition and anti-tumor activity of D. officinale grown in the Huoshan area are largely unknown.MethodsA polysaccharide (DOPA-1) was isolated from D. officinale by hot water extraction and ethanol precipitation, followed by purification via DEAE-cellulose and Sephadex G-100 chromatography. DOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Polysaccharides and proteins are usually collected from the precipitate of EPP. The polysaccharides of TCMs may possess antioxidant activity [35,36], anti-tumor activity [37], immunomodulatory effects [38], and hepatoprotective effect [39]. By adjusting the ethanol concentration in supernatant, polysaccharides with different molecular weight distributions can be obtained.…”
Section: Epp Application For Bioactive Component Purificationmentioning
confidence: 99%
“…Polysaccharides and proteins are usually collected from the precipitate of EPP. The polysaccharides of TCMs may possess antioxidant activity [35,36], anti-tumor activity [37], immunomodulatory effects [38], and hepatoprotective effect [39]. By adjusting the ethanol concentration in supernatant, polysaccharides with different molecular weight distributions can be obtained.…”
Section: Epp Application For Bioactive Component Purificationmentioning
confidence: 99%
“…Dendrobium officinale , a plant that grows on rocky cliffs, is mainly distributed in Southwestern Anhui, Eastern Zhejiang, Western Fujian, Northwestern Guangxi, Sichuan and Southeastern Yunnan of China [1, 2]. Dendrobium officinale has anti-tumor, anti-fatigue and anti-oxidation properties [3, 4, 5]. Modern studies show that Dendrobium officinale contains a variety of chemical constituents, and the types of compounds identified so far include alkaloids, carbohydrates, bibenzyls, steroidal saponins, and flavonoids [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al reported that polysaccharide isolated from Dendrobium officinale had anti-tumor activity on HepG-2 cells by MTT assay. 26 The growth inhibitory rates of the crude polysaccharides to human gastric cancer cells were evaluated in vitro by MTT assay. 3 The polysaccharide of strain FK1 was extracted from the mycelium free supernatant by boiling water method and evaluated for antitoxicity effect on two human cancer cell lines: HeLa cell line and lymphoblastoid cell line (LCL) by MTT method.…”
Section: Introductionmentioning
confidence: 99%